Distribution of Rare Elements in Tactites of North-East and North-West Area of Dashkasan Iron Ore Deposit - Gubadov, R.R.; Guseinov, G.S.; Aliyarov, R.Y. (Herald of Azerbaijan Engineering Academy, 2025)
In the article, the distribution of rare elements in the tactites of the North-East and North-West areas of the Dashkasan iron ore deposit was considered. Test samples were taken from the mentioned areas. As a result of the conducted research, it was determined that among the rare elements, Nb, La, Ce, Gd are found in tactite carbonates, veins and secondary altered high amounts are observed in minerals - diopside, magnetite, actinolite, andradite. It should be noted that the amount of Nb and La in calcium tactites is 1258.3 and 2820 ppm. The high amount of lanthanides is 5131 and 1478 ppm. Dashkasan The analysis results of the tests taken from the North-East and North-West areas of the iron ore deposit provide a basis for studying the formation conditions of the deposit. The results obtained in the research area are important in the preparation of forecast-search factors. The analysis results of the studied ores are shown in the article by means of tables.